Francisella tularensis Subspecies holarctica, Tasmania, Australia, 2011 - Justin Jackson; Alistair McGregor; Louise Cooley; Jimmy Ng; Mitchell Brown; Chong Wei Ong; Catharine Darcy; Vitali Sintchenko (Emerging Infectious Diseases, 2012)
We report a case of ulceroglandular tularemia that developed in a woman after she was bitten by a ringtail possum (Pseudocheirus peregrinus) in a forest in Tasmania, Australia. Francisella tularensis subspecies holarctica was identified. This case indicates the emergence of F. tularensis type B in the Southern Hemisphere.